App-based collective transport service in Mexico City: A start-up case study - Onésimo Flores Dewey (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
This paper details the history of Jetty, an app-based collective transport platform operating in Mexico City since August 2017. It sets out the origins of the idea, recounts the strong competitive and regulatory pushback Jetty has faced, and evaluates Jetty's current growth and impact. In this context, the paper explores the potential contribution of new app-based mobility services in environments such as Mexico City - where transit alternatives are ubiquitous, fares are low and unsubsidised, but service is unsafe, insecure, uncomfortable, unreliable and unaccountable. It asks to what extent a technology company can complement government regulations, by establishing and enforcing stricter service standards on private suppliers of service whilst remaining responsive and accountable to passengers.
Keywords: 330; Taxigewerbe; Öffentlicher Nahverkehr; Share Economy; Transportrecht; Mobile Anwendung; Mexiko-Stadt; Mexiko